Inovasi Nugget Ikan Patin: Solusi Meningkatkan Pertumbuhan dan Perkembangan Anak serta Pencegahan Stunting di Desa Handil Birayang Bawah Kecamatan Bumi Makmur Kabupaten Tanah Laut - Abdullah, Abdullah; Norfai, Norfai; Riza, Yeni; Rahman, Eddy (Jurnal Abdimas Kesehatan (JAK), 2025)
Stunting remains a chronic nutritional problem in Indonesia, particularly in rural areas, influenced by low intake of animal protein due to limited parental knowledge of balanced nutrition and restricted access to quality food sources. Catfish (Pangasius) as a local commodity rich in protein, essential fatty acids, and micronutrients has the potential to be an effective solution. However, children’s low interest in consuming fresh fish hinders its optimal utilization. Therefore, this community service program was implemented in Handil Birayang Bawah Village, Bumi Makmur District, Tanah Laut Regency, with the aim of improving community knowledge and skills in utilizing animal protein for stunting prevention. The innovation introduced was catfish nuggets, a nutritious processed food preferred by children. The activities included preparation (identifying materials and tools, preparing educational materials, and coordinating with PKK cadres), implementation (nutrition education, catfish nugget training, joint practice, and product trials). The program was carried out effectively, as evidenced by the increased knowledge of PKK cadres, reflected in their enthusiasm during discussions and question-and-answer sessions. Furthermore, their skills in food processing, particularly in making catfish nuggets, improved through active participation and successful practice. This innovation utilizes local potential while providing a practical and appealing nutritious food alternative, thereby contributing to child growth and stunting prevention